2020
DOI: 10.12962/j2580-0914.v4i1.8706
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Effect of Variation in Shielding Gas Flow Rate and V Groove Type Towards Tensile and Metallographic Testing of GMAW Weld Joint of ASTM A53 and A36

Abstract: Steel is a metal that commonly used in fabrication, engineering, and reparation activities in the structure construction industry. ASTM A53 steel is a low carbon steel with 0.25% to 0.3% of carbon content so it has a high weldability. ASTM A36 steel is a low carbon steel with carbon content of 0.25% to 0.29% and is often used in the floating building industry. This study aims to determine the effect of shielding gas flow rate and V-groove type to the tensile strength of A53 steel welded with A36 steel by Gas M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Shuo et al 34 optimized the V groove angles of the butt weld joint of a 12 mm thick dissimilar welded plate of P92 steel/super 304H using TP304H as filler and observed 20° groove angle was the optimal groove angle for the weld plate joint, considering mechanical properties for as-welded and PWHT condition. Pratikno et al 35 compared butt weld joints of different groove geometry and found better tensile properties for DVG joints than single V groove joints. Li et al 36 analyzed the residual stress on the top and the bottom surface of two butt weld joints (single-V groove and double-V groove) made between 10 mm plates of P92 and SUS304 steel, using the hole-drill strain gauge method.…”
Section: Introductionmentioning
confidence: 99%
“…Shuo et al 34 optimized the V groove angles of the butt weld joint of a 12 mm thick dissimilar welded plate of P92 steel/super 304H using TP304H as filler and observed 20° groove angle was the optimal groove angle for the weld plate joint, considering mechanical properties for as-welded and PWHT condition. Pratikno et al 35 compared butt weld joints of different groove geometry and found better tensile properties for DVG joints than single V groove joints. Li et al 36 analyzed the residual stress on the top and the bottom surface of two butt weld joints (single-V groove and double-V groove) made between 10 mm plates of P92 and SUS304 steel, using the hole-drill strain gauge method.…”
Section: Introductionmentioning
confidence: 99%